Restoring Culture of Ethics & Values: The Holistic Education Way - Sarkar, Manju (International Journal of Psychosocial Rehabilitation, 2020)
In present time, it’s a common philosophy that unless you love yourself, you cannot love others. Quite the reverse: if it were the true self, that would be different, but those who proclaim this mean to love themselves, their ego and mind. That is the travesty or perversion of this Kali Yug. The only language through which we can unite with the true self is the meaning of unconditional love with God. The only language through which we can unite with the true self is the meaning of unconditional love with God. Every other love is conditioned and therefore selfish, possessive, and attached, which brings in insecurity and weakness. Eat, look after your family, earn money, be charitable, use your talents, and sing all the action only for ‘god’s sake.’